1997
DOI: 10.1109/77.621741
|View full text |Cite
|
Sign up to set email alerts
|

Single flux quantum circuits for 2.5 Gbps data switching

Abstract: A~s~~a c~-~e have designed and measured) circuits for data Gbps. A fully functional 2x2 presented. The node can be used s w i t~h~n~ fabric (4x4, 8x8, etc.). ata streams at either or both ased on address bits stream. This approach allows outing and the switch to be addition, the switch can an active input line if the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…136 While optical crosspoints are not fast enough for this, it is well within the capability of today's RSFQ circuits. 137 In fact, one analysis has shown that a 128x128 channel self-routing Batcher-Banyan switching core implemented in a 0.8-um RSFQ technology could provide throughput close to 100 Gbit per channel, dissipate about 10 mW of power, and fit on a single 1-cm 2 die. 138 …”
Section: Network Switchesmentioning
confidence: 99%
“…136 While optical crosspoints are not fast enough for this, it is well within the capability of today's RSFQ circuits. 137 In fact, one analysis has shown that a 128x128 channel self-routing Batcher-Banyan switching core implemented in a 0.8-um RSFQ technology could provide throughput close to 100 Gbit per channel, dissipate about 10 mW of power, and fit on a single 1-cm 2 die. 138 …”
Section: Network Switchesmentioning
confidence: 99%